Design of Medical Devices to Monitor Body Temperature, Heart Rate And Oxygen Saturation Levels In Human Body Based On IoT - Ihsan, Muhammad Nabil; Taqwa, Ahmad; Ciksadan, Ciksadan (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Understanding body temperature and heart rate plays a crucial role in detecting disease symptoms. Heart rate serves as a vital parameter reflecting human body function, with a typical range of 60-100 beats per minute for adults. This study aims to leverage Internet of Things (IoT) technology to create a monitoring system for heart rate and body temperature.The main objective of this final project is to design a device capable of monitoring body temperature, heart rate, and oxygen saturation levels in the human body. The anticipated benefits of this research include facilitating the continuous monitoring of body temperature, heart rate, and oxygen saturation levels, thus aiding in timely health assessments. To achieve this, the study employs the MLX90614 sensor for temperature measurement and the MAX30100 sensor for heart rate and oxygen saturation level readings. These sensors are integrated with the Arduino Nano microcontroller and NodeMCU ESP8266.The study's findings demonstrate that the sensors effectively measure body temperature, heart rate, and oxygen saturation levels, as confirmed by comparison with medical-grade devices. The system developed in this research performs well and is ready for practical application, providing the desired benefits of enhanced monitoring capabilities for healthcare purposes.